Roles and mechanisms of circular RNAs in lung diseases caused by environmental exposure - Hangjun LUO; Qian BIAN (环境与职业医学, 2022)
Environmental exposure is an important factor in the occurrence and development of various lung diseases. Circular RNAs (circRNAs) are a class of noncoding RNA molecules, which are widely expressed in eukaryotes, and have been proved to play an important role in the occurrence and progression of a variety of human diseases. Studies have shown that circRNAs are closely related to various lung diseases, and have been used as diagnostic and prognostic biomarkers and therapeutic targets of some lung diseases. This review briefly described the physiological functions and molecular mechanisms of circRNAs, and summarized the regulatory mechanisms of circRNAs in lung diseases caused by environmental exposure, in order to provide new ideas for the research and application in related fields in the future.